2-N-alquilpiridilporfirinas de Mn(III) como modelos tiol (per)oxidases e agentes terapêuticos redox ativos em modelo animal de câncer de mama e modelo vegetal de estresse salino - Jesus, Jacqueline Cristina Bueno Janice de (2020)
Mn(III) 2-N-alkylpyridylporphyrins are redox-active compounds that can react with different reactive species and reducing agents present in the biological milieu. These coordination compounds have been intensively studied as biomimetic catalysts and redox-active therapeutics in several diseases and systems of biotechnological interest associated with oxidative stress. In this thesis, four independent studies were carried out centered on exploring the Mn(III) 2-Nalkylpyridylporphyrins as biomimetic catalysts and redox-active therapeutics; the use of Mnporphyrins in a plant model of saline stress was described for the first time. Initially, an alternative route for obtaining two Mn(III) 2-N-alkylpyridilporphyrins, Mn(III) mesotetrakis( N-ethylpyridinium-2-yl)porphyrin (MnTE-2-PyPCl5) and Mn(III) meso-tetrakis(N-nhexylpyridinium- 2-yl)porphyrin (MnTnHex-2-PyPCl5), was investigated using Mn(III) mesotetrakis( 2-pyridyl)porphyrin chloride (MnT-2-PyPCl) as intermediate. A new methodology for the synthesis of MnT-2-PyPCl in aqueous acidic medium was developed with purification with no organic solvents. The catalytic activity of MnTE-2-PyP5+ and a series of other redox-active compounds for thiol oxidation as biomimetic models of the thiol peroxidase and oxidase enzymes was evaluated. MnTE-2-PyP5+ presented the highest rates for the oxidation of glutathione and other thiols; additionally, spectrophotometric and electrochemical studies of the reactions showed the participation of O2 in these systems. Furthermore, to explore the action of Mn(III) 2-N-alkylpyridylporphyrins in in vivo oxidative stress-related models, studies were carried in animal and plant models. The combined use of MnP with other antitumoral treatments, such as ascorbate (Asc) and radiotherapy (RT), was investigated in a Balb/C mice breast cancer model, using three distinct MnPs: MnTnBuOE-2-PyP5+, MnTE-2-PyP5+ e MnTBAP3–. Additionally, bioaccumulation in tumor, muscle and liver tissues were analyzed by LC-MS/MS technique. The cationic MnPs were very efficient in enhancing the effects of Asc+RT treatments in reducing tumor growth, with tumor inhibition of ~73% in relation to the control. Similar results of these cationic MnPs are justified by their similar redox and reactivity properties and accumulation in the target tissue (tumor) in the same order of magnitude. For the first time a bioaccumulation study of MnTBAP3– using the LC-MS/MS technique was performed. Although the anionic MnP did not present therapeutic effect in the studied model, it bioaccumulated in the tumor ~20-fold more than cationic MnPs did. Finally, in order to expand the studies of MnPs in in vivo models, a plant model of laboratory cultivation was developed for the Wray variety of sweet sorghum [Sorghum bicolor (L.) Moench] under saline stress, in hydroponic medium. Effects of various levels of MnTE-2-PyPCl5 on initial plant development under saline stress (100 mmol L–1 of NaCl) and without saline stress (8 mmol L-1 of NaCl) were studied, assessing parameters such as plant height, biomass, and dry mass. Among the MnP concentration range tested (0–100 μmol L–1), the analysis of variance showed significant positive effects on plant height associated with treatment with 10 μmol L–1 MnTE- 2-PyPCl5 in plants under salt stress. Analysis of dry mass parameters indicated that MnP at 100 μmol L–1 concentration limited the development of sweet sorghum at both levels of salinity, pointing to a slight toxicity of MnTE-2-PyPCl5 at high concentration. This study represented the first use of MnP-based redox modulators for attenuation plant growth associated with of saline stress.